PHYTOCHEMICAL, MICROBIOLOGICAL, AND TECHNOLOGICAL STUDIES IN THE FIELD OF OBTAINING A HYDROALCOHOLIC EXTRACT WITH ANTIMICROBIAL ACTIVITY FROM THE LIQUORICE ROOT - Boyko, Nikolay; Tkachev, Alexandr; Kovalenko, Anatoliy; Pisarev, Dmitriy; Kuznietsova, Victoria; Sushchuk, Natalia; Bondarev, Alexandr (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this work was to carry out studies in the field of development of a hydroalcoholic extract from the liquorice root that has a high level of antimicrobial activity. Methods: For the antibacterial study of extracts, we have used the agar well diffusion method. In our research, we have utilized six test-strain microorganisms: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Proteus vulgaris ATCC 4636, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885/653, and Bacillus subtilis ATCC 6633. Authors have applied vector theory for antimicrobial activity comparison of liquorice root extracts. Results: Phytochemical composition and antimicrobial activity of hydroalcoholic extracts from the liquorice root with the use of different concentrations of ethanol have been studied. The optimal range of ethanol concentration of 65Â±15% v/v has been found. The dependency between the integral index of antimicrobial activity of the extract and concentration of glycyram and licuroside has been found. The minimal concentration of glycyram and licuroside in the extract has been calculated for an exhibition of the target level of extract’s antimicrobial activity, which is 1.0 and 0.11% w/v, respectively. Conclusion: It has been found that the concentration of licuroside has greater influence on the integral index of extract’s antimicrobial activity in comparison with that one of glycyram. A highly effective technology for obtaining an extract with target phytochemical parameters has been suggested.